Evaluation of the standard for taking off orthodontic devices fixed with hydrophylic and hydrophobic adhesive: A literature review (Research, Society and Development, 2021)
A problem commonly encountered, both by the surgeon and by the orthodontist, during the traction of included teeth, is the difficulty in performing the fixation and maintenance of orthodontic accessories in the tooth, since this is generally a humid environment due to the presence of oral fluids. Therefore, the purpose of this study was to carry out a narrative-type literature review on the pattern of orthodontic device take-off, adhered to the dental element with hydrophilic and hydrophobic adhesive systems. For this purpose, a search was carried out in the Scielo, PubMed, Google Scholar and Portal BVS databases between the years 2008 and 2021. The type of fracture from mechanical tests was evaluated, which was subsequently analyzed using optical microscopy. After applying the inclusion and exclusion criteria, nine articles were selected, which showed a higher percentage of adhesive failures. Therefore, the researched adhesives can be used in bonding brackets, both in wet and dry environments, as they have sufficient bond strength to be an orthodontic adhesive.